AquaNet - 18S Eukaryotes Reads from Bolmen AquaNet platform, 2017-06-21–2017-09-19 - Bolmen Research Station (Swedish University of Agricultural Sciences, 2019)
Mesocosm experiment focusing on fish pulse and light reduction as treatment effects ran simultaneously at the SITES stations Asa, Erken, Skogaryd, Svartberget and Bolmen during summer 2017. Data contains number of reads per Operational Taxonomic Unit of 18S Eukaryotes.
Bolmen Research Station (2019). AquaNet - 18S Eukaryotes Reads from Bolmen AquaNet platform, 2017-06-21–2017-09-19 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/IynhhVTAcIMwZ1AdMxq_xmDp
Keywords: SITES AquaNet; Ecosystem functions; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap